Bioresource from the French Gazel Cohort Study. (24th July 2014) - Goldberg, Marcel; Henny, Joseph; Leclerc, Annette; Zins, Marie
The GAZEL Cohort Study set up in 1989 is a general-purpose epidemiologic cohort. At inception in 1989, the cohort included 20, 625 volunteers then aged from 35-50 (women; n= 5, 614) or 40-50 (men; n= 15, 011). The data collected routinely come from different sources, mainly annual self-administered questionnaires, socioeconomic and health administrative data, health examinations, and causes of death. The epidemiologic database is maintained and stored by our group in our own facilities; the biobank is stored in the "Centre de ressources biologiques", in Dijon, France. Today, more than 50 epidemiological projects on diversified themes have been set up in the GAZEL Cohort Study by some 30 French and foreign teams.